2011
DOI: 10.1038/leu.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic signaling activity of the anti-CD40 monoclonal antibody dacetuzumab circumvents multiple oncogenic transformation events and chemosensitizes NHL cells

Abstract: Non-Hodgkin lymphoma (NHL) is a genetically heterogeneous disease with several oncogenic events implicated in the transformation of normal developing B lymphocytes. The objective of this study was to elucidate the signal transduction-based antitumor mechanism(s) of action for the anti-CD40 monoclonal antibody dacetuzumab (SGN-40) in NHL. We report that dacetuzumab activates two distinct proapoptotic signaling pathways, overcoming transformation events key to the pathogenesis of NHL. Dacetuzumab-mediated CD40 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
16
1
Order By: Relevance
“…We have previously shown that activation of the NF-kB and MAP kinase pathways is important to the cytotoxicity of dacetuzumab in cultured NHL cell lines (24). Therefore, we contrasted the relative ability of dacetuzumab to activate signal transduction through these signaling cascades with that of rituximab (Fig.…”
Section: Dacetuzumab and Rituximab Have Cell Line-specific Differencementioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that activation of the NF-kB and MAP kinase pathways is important to the cytotoxicity of dacetuzumab in cultured NHL cell lines (24). Therefore, we contrasted the relative ability of dacetuzumab to activate signal transduction through these signaling cascades with that of rituximab (Fig.…”
Section: Dacetuzumab and Rituximab Have Cell Line-specific Differencementioning
confidence: 99%
“…Our group has previously reported that dacetuzumab causes a sustained downregulation of the BCL-6 oncoprotein and upregulates the proapoptotic p53 family member TAp63a in NHL cell lines (24). Because rituximab and dacetuzumab activate similar signaling pathways in 2/3 cell lines, we evaluated the ability of rituximab to affect BCL-6 and TAp63a expression (Fig.…”
Section: Dacetuzumab and Rituximab Have Cell Line-specific Differencementioning
confidence: 99%
See 2 more Smart Citations
“…models 8 and SGN-40 in combination with Rituximab and gemcitabine in a SGN-40 phase Ib trial where 54% (15 out of 28) of patients with DLBCL experienced an objective response. 9 Similarly, CP-870,893, another anti-CD40 agonist antibody, combined with gemcitabine elicited potent tumor shrinkage in a subset of pancreatic cancers, although in this case macrophages were reported to be responsible for the efficacy.…”
mentioning
confidence: 99%